2007
DOI: 10.1093/nar/gkm671
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of multiple DNA dyes for real-time PCR: effects of dye concentration and sequence composition on DNA amplification and melting temperature

Abstract: The importance of real-time polymerase chain reaction (PCR) has increased steadily in clinical applications over the last decade. Many applications utilize SYBR Green I dye to follow the accumulation of amplicons in real time. SYBR Green I has, however, a number of limitations that include the inhibition of PCR, preferential binding to GC-rich sequences and effects on melting curve analysis. Although a few alternative dyes without some of these limitations have been recently proposed, no large-scale investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
224
2
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 266 publications
(239 citation statements)
references
References 36 publications
12
224
2
1
Order By: Relevance
“…The Tm values obtained in this experiment are higher than those in the AuNP case because SYBR Green I is known to increase DNA Tm. 60 To confirm our conclusion, we also did an independent experiment where the hyperchromic effect of DNA melting at 260 nm was measured (see…”
Section: Melting As a Function Of Gap Size One Of The Most Importantmentioning
confidence: 66%
“…The Tm values obtained in this experiment are higher than those in the AuNP case because SYBR Green I is known to increase DNA Tm. 60 To confirm our conclusion, we also did an independent experiment where the hyperchromic effect of DNA melting at 260 nm was measured (see…”
Section: Melting As a Function Of Gap Size One Of The Most Importantmentioning
confidence: 66%
“…This was possible by using a real-time turbidimeter 22 or by measuring the signals from DNA produced via fluorescent intercalating dyes 21,23 . Fluorescent detection is by far the most sensitive method, however, in a previous study, the intercalating dyes were shown to partially or completely inhibit PCR-based amplification, which compromised the advantages of using fluorescence measurement 24 . To our best knowledge, only a limited number of intercalating dyes such as SYTO 9 21 , SYTO 82 14 or SYBR Green 21 have been used rtLAMP.…”
Section: Comparison Of Multiple Dna Intercalating Dyes For Real-time mentioning
confidence: 98%
“…Non-target amplifications resulting from primer-dimer artefacts were produced in the absence of template molecules in both negative control and unknown samples. They were excluded from the results through melt-curve analysis (Gudnason et al 2007). A subset (n = 8) of positive samples were confirmed as wood frog DNA via Sanger sequencing (GenBank accession #MG002391-MG002398).…”
Section: Abstract Edna · Wood Frog · Rana Sylvatica · Cytochrome B · mentioning
confidence: 99%